Microsoft Word 2002 for law firms - Payne Consulting Group; Inc (Prima Tech, 2001)
This comprehensive guide won't waste your time with features irrelevant to the legal community. Microsoft Word 2002 software contains features that finally meet the requirements that law firms and legal departments have been asking about for years. And this book explains them all! It provides industry-specific information about Word 2002 to help you operate effectively and efficiently in your legal environment. Whether you are completely new to Word or simply updating to the newest version, this book will increas your productivity and guide you to making the most of this new software